let $a_0$ and $a_1$ be any two real numbers, and define

$a_n= \dfrac{a_{n-1} + a_{n-2}}{2}$

Determine the convergence of a sequence.

Alright, what I have so far. I have two cases $a_0$ > $a_1$ or $a_0$ < $a_1$

for $a_0 > a_1$

The sequence converges to $\frac{1}{3}$($a_0 - a_1$) + $a_0$

for $a_0 < a_1$

The sequence converges to $\frac{2}{3}$($a_1 - a_0$) + $a_0$

Any additional input?

  • $\begingroup$ Are you just supposed to determine whether it converges, or what the limit is? Your question seems to be about the former. $\endgroup$ – robjohn Mar 4 '14 at 23:57
  • $\begingroup$ I'm supposed to determine the limit, sorry for the he ambiguity. $\endgroup$ – Benji_Bombadill Mar 4 '14 at 23:59
  • $\begingroup$ Why is the answer for $a_0\gt a_1$ different than the answer for $a_0\lt a_1$? $\endgroup$ – robjohn Mar 5 '14 at 0:31
  • $\begingroup$ I posted an overkill solution involving generating functions. Let me know if I need to clarify stuff. ~R $\endgroup$ – Rustyn Mar 5 '14 at 1:06
  • $\begingroup$ Additional input: you have the answer, but not the proof that it works. In a math course, that may mean you get zero credit... $\endgroup$ – GEdgar Aug 10 '17 at 13:16

Hint 1: $$ a_n-a_{n-1}=-\tfrac12(a_{n-1}-a_{n-2}) $$ Show by induction that $$ a_n-a_{n-1}=\left(-\tfrac12\right)^{n-1}(a_1-a_0) $$ Hint 2: $$ a_n=a_0+\sum_{k=1}^n\left(-\tfrac12\right)^{k-1}(a_1-a_0) $$


$a_n = \dfrac{a_{n-1}+a_{n-2}}{2}$. One overkill way of finding the limit, is getting the $a_n$ in terms of $n$ via a generating function.

Write $F(x) = \sum_{i=0}^{\infty}a_i x^i$. Thus,

$$ \frac{F(x)-a_0}{x}=\sum_{i=0}^{\infty}a_{i+1}x^{i} $$ $$ \frac{F(x)-a_0-a_1}{x^2} = \sum_{i=0}^{\infty}a_{i+2}x^{i} $$ So, $$ \frac{F(x)-a_0-a_1}{x^2} = \frac{1}{2}\cdot \frac{F(x)-a_0}{x} + \frac{1}{2}F(x) $$ Solving for $F(x)$, one obtains: $$ \frac{(x-2)a_0-2a_1}{x^2+x-2}=F(x) $$ Using partial fractions, one then obtains: $$ F(x) = \frac{-(a_0+2a_1)}{3(x-1)}+\frac{2(2a_0+a_1)}{3(x+2)} $$ Now write each term as a power series, obtaining: $$ F(x) =\frac{(a_0+2a_1)}{3}\sum_{k=0}^{\infty} x^k +\frac{(2a_0+a_1)}{3}\sum_{k=0}^{\infty} \left(-\frac{1}{2}\right)^k(x)^k $$

Now, $a_{n+1}$ is the $(n+1)^{st}$ coefficient and therefore the coefficient of $x^n$ given above. Explicitly, $$ a_{n+1} = \frac{(a_0+2a_1)}{3}+\frac{(2a_0+a_1)}{3}\left(\frac{-1}{2}\right)^n $$ e.g. if $a_0=0, a_1=1$, we have: $$ a_2=\frac{1}{2},a_3=\frac{\frac{1}{2}+1}{2}=\frac{3}{4},a_4=\frac{\frac{3}{4}+\frac{1}{2}}{2}=\frac{5}{8} $$ Now we expect that $$a_4 = \frac{(a_0+2a_1)}{3}+\frac{(2a_0+a_1)}{3}\left(\frac{-1}{2}\right)^3 = \frac{5}{8}$$ And $$ \frac{(a_0+2a_1)}{3}+\frac{(2a_0+a_1)}{3}\left(\frac{-1}{2}\right)^3= \\\frac{2}{3}+\frac{1}{3}\left(\frac{-1}{2}\right)^3=\frac{5}{8} $$

Now, it is easy to see that $$ \lim_{n\to \infty}a_{n+1} = \lim_{n\to \infty} \frac{(a_0+2a_1)}{3}+\frac{(2a_0+a_1)}{3}\left(\frac{-1}{2}\right)^n = \frac{(a_0+2a_1)}{3} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.